Emotionality and Valence in Autobiographical Remembering - Sezin Öner (Psikiyatride Güncel Yaklaşımlar, 2021)
Current review focused on the effects of emotionality and valence of experienced events on their memorability and the phenomenology of remembering both in its theoretical context and in terms of empirical evidence. Different ways how remembering operates in post-traumatic stress disorder, flashbulb memories, and mood disorders are discussed using evidence from behavioral and neuroimaging studies. On the basis of the evidence, an integrated perspective is presented for future research on the relationship between autobiographical recollection and the emotional content and valence of events.